Comparative analyses of clinical and environmental populations of Cryptococcus neoformans in Botswana. Issue 14 (7th July 2015) - Chen, Yuan; Litvintseva, Anastasia P.; Frazzitta, Aubrey E.; Haverkamp, Miriam R.; Wang, Liuyang; Fang, Charles; Muthoga, Charles; Mitchell, Thomas G.; Perfect, John R.
Abstract Cryptococcus neoformans var. grubii (Cng) is the most common cause of fungal meningitis, and its prevalence is highest in sub‐Saharan Africa. Patients become infected by inhaling airborne spores or desiccated yeast cells from the environment, where the fungus thrives in avian droppings, trees and soil. To investigate the prevalence and population structure of Cng in southern Africa, we analysed isolates from 77 environmental samples and 64 patients. We detected significant genetic diversity among isolates and strong evidence of geographic structure at the local level. High proportions of isolates with the rare MATa allele were observed in both clinical and environmental isolates; however, the mating‐type alleles were unevenly distributed among different subpopulations. Nearly equal proportions of the MATa and MATα mating types were observed among all clinical isolates and in one environmental subpopulation from the eastern part of Botswana. As previously reported, there was evidence of both clonality and recombination in different geographic areas. These results provide a foundation for subsequent genomewide association studies to identify genes and genotypes linked to pathogenicity in humans.